2013
DOI: 10.1007/s00059-013-3865-4
|View full text |Cite
|
Sign up to set email alerts
|

Coronary vessel diameters during and after primary percutaneous coronary artery intervention

Abstract: This study showed that RVD was higher at the follow-up CAG a few days after AMI in patients who had TIMI 3 flow after P-PCI with simple balloon dilatation and/or thrombus aspiration. A delay of a few days for stent implantation in P-PCI allows for larger-diameter stent use and may help to reduce stent thrombosis and restenosis rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
3
5
0
Order By: Relevance
“…Infarct versus non-infarct setting was the only significant independent predictor of change in non-culprit stenosis. PDS was decreased significantly in our study consistent with the observations of Hanratty et al [8] and Sahin et al [19] MLD was increased and PDS was decreased significantly in our study on follow-up CAG. Hanratty et al [8] and Sahin et al [19] also reported similar significant changes in MLD and PDS.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Infarct versus non-infarct setting was the only significant independent predictor of change in non-culprit stenosis. PDS was decreased significantly in our study consistent with the observations of Hanratty et al [8] and Sahin et al [19] MLD was increased and PDS was decreased significantly in our study on follow-up CAG. Hanratty et al [8] and Sahin et al [19] also reported similar significant changes in MLD and PDS.…”
Section: Discussionsupporting
confidence: 92%
“…They also found that there was no significant change in lesion length. RVD was increased significantly on follow-up CAG in our study similar to the reported by Sahin et al [19] However, Hanratty et al [8] and Cristea et al [20] found that there was no change in RVD. Hanratty et al [8] included 48 patients with 59 non-culprit lesions suitable for analysis in their study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It is important to note that all patients responded well to PCI after the transient vasoconstriction incident. Moreover, multiple confounding factors may contribute to vasoconstriction during PCI, including the milieu of acute myocardial infarction itself 38 , 39 . In our experiments with long tone burst ultrasound (5,000 μs), we did observe a several minute delay in microvascular reperfusion following SRP therapy, which in the intact hindlimb was restored and returned to levels above baseline perfusion after 5 min.…”
Section: Discussionmentioning
confidence: 99%
“…25 Myocardial ischaemia is known to stimulate catecholamine release and the renin-angiotensin system, resulting in systemic vasoconstriction proportional to the degree of ischaemia. 26 Mirroring this is the vasoconstriction seen in the coronary vessels during infarction, 27 and so systemic hypertension represents greater ischaemia and increased vasoconstriction, resulting in higher levels of ischaemic and perfusion injury contributing to NR.…”
Section: Risk Scorementioning
confidence: 99%